2005
DOI: 10.2975/28.2005.315.322
|View full text |Cite
|
Sign up to set email alerts
|

Moving Forward: Negotiating Self and External Circumstances in Recovery.

Abstract: This article presents a framework for understanding the concept of recovery from serious mental illnesses and other life struggles. The framework is based on findings from a longitudinal, qualitative study that involved in-depth interviews with 28 people who experienced serious mental health challenges. The purpose of this article is to clarify the concept of recovery by presenting a grounded theory analysis of the components of recovery. The framework recognizes the experiences of struggle constructed through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
76
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 21 publications
(66 reference statements)
9
76
0
Order By: Relevance
“…While it is not clear why there was a regression to baseline levels at the 18-month follow-up, these findings indicate that improvement in the context of consumer-run organizations is not a linear process. This is consistent with the emerging literature on recovery, which has emphasized that the recovery process includes setbacks, as well progress~Ochocka, Nelson, & Janzen, 2005!. Another interesting finding from this research is that only the group that participated continuously and intensively in CSIs showed benefits in terms of community integration, quality of life~daily activities!, symptom distress, and employment0 education. The continuously active group participated 10-12 hours per month during the first 16 months of the study and the last 6 months of the study, while the group that was active only at 9 and 18 months participated only 3 hours per month during the first 16 months of the study.…”
Section: Discussionsupporting
confidence: 78%
“…While it is not clear why there was a regression to baseline levels at the 18-month follow-up, these findings indicate that improvement in the context of consumer-run organizations is not a linear process. This is consistent with the emerging literature on recovery, which has emphasized that the recovery process includes setbacks, as well progress~Ochocka, Nelson, & Janzen, 2005!. Another interesting finding from this research is that only the group that participated continuously and intensively in CSIs showed benefits in terms of community integration, quality of life~daily activities!, symptom distress, and employment0 education. The continuously active group participated 10-12 hours per month during the first 16 months of the study and the last 6 months of the study, while the group that was active only at 9 and 18 months participated only 3 hours per month during the first 16 months of the study.…”
Section: Discussionsupporting
confidence: 78%
“…More recently, Jacobson and Greenley [4] addressed a multi-dimensional concept of recovery consisting of internal conditions such as hope, healing, empowerment, and connection, as well as external conditions such as human rights, a positive culture of healing, and recovery-oriented services. Noordsy et al [24] [12]. In addition, a few tools were developed to measure subjective aspects of recovery.…”
Section: Hermeneutics and Phenomenological Perspectivementioning
confidence: 99%
“…This changed view about the course of schizophrenia can be accounted by not only the introduction of antipsychotic drugs, but many other factors such as a landmark study on the prognosis of schizophrenia conducted by Harding, Brooks, Ashikaga, Strauss, & Breier [3], studies on a new definition of recovery from severe mental disorders by Anthony [2] and Jacobson & Greenly [4], and numerous qualitative studies about lived experience of people with schizophrenia [5]- [12].…”
mentioning
confidence: 99%
“…Instead, recovery has been ruminated upon in mental health circles and within substance misusing groups without a criminal background (e.g. Hänninen & Koski-Jännes, 1999;Hughes, 2007;Nettleton, Neale & Pickering, 2010;Ochocka, Nelson & Janzen, 2005;Vigilant, 2005).…”
Section: Introductionmentioning
confidence: 99%